Initial Task Engagement: Unlocking the Value of Fit and Non-Fit to Improve Audit Judgments - Hong, Bright (Yue) (The Accounting Review, 2022)
ABSTRACT Deficiencies identified in complex audit tasks suggest room for improvement in audit judgments. I propose that aligning an auditor's focus (prevention/promotion) and mindset (concrete/abstract) in a compatible way can induce an experience of “regulatory fit” that improves judgments compared to “regulatory non-fit.” Results are more complex than previously thought. I find that fit versus non-fit improves judgments, but only for auditors who are initially less engaged in the judgment task. For auditors who are initially more engaged, non-fit versus fit improves judgments. A second experiment provides converging evidence. Prior research finds strong evidence that fit improves performance versus non-fit. The possibility that non-fit could improve performance has received little attention. By conceptualizing initial task engagement and identifying it as a key moderator, my study suggests that non-fit also has value, and that assessing auditor preexisting conditions before prescribing interventions is important for improving judgments.